Experimental investigation of bond characteristics of deformed and plain bars in low strength concrete - Ahmad, Sohaib; Pilakoutas, Kypros; Rafi, Muhammad Masood; Khan, Qaiser Uz Zaman; Neocleous, Kyriacos (My University, 2018)
The use of inferior quality materials, inadequate detailing, and poor construction practices are responsible for most of brittle failure modes of non-engineered reinforced concrete structures. Bond failures in non-engineered reinforced concrete elements, due to short anchorages or low concrete cover result in large slip deformations, prevent the development of plastic deformations and reduce energy dissipation capacity. Until now, few research works have been carried out that could facilitate the development of bond-slip relationships for low strength non-engineered reinforced concrete structures. To address this, experiments were carried out on pull-out and splitting specimens under monotonic loading to investigate bond characteristics of typically used steel bars in nonengineered reinforced concrete structures. Various deficient parameters were considered in the experiments in order to develop multi-parameter bond strength relations for low strength concrete ≤ 15 MPa. The key parameters examined in the experiments include low strength concrete, bar development length, concrete cover, rebar types (deformed and plain), and rebar diameter. This paper presents the experimental details and results, which are further processed to develop bond strength equations for different bar types in low strength concrete. These equations can be used to define the bond-slip relation for conducting seismic vulnerability assessment of non-engineered structures.
Keywords: Low strength concrete; Normal strength concrete; Non-engineered reinforced concrete; Reinforced Concrete; Bond-slip; Deformed bar